International Students in China: Facts, Paths, and Challenges - Yang, Zhou; de Wit, Hans (International Higher Education, 2019)
This article is based on a report released by China’s ministry of education, indicating that more than half of the country’s international students come from Asian countries, with Korea sending the most students. International students in China are mostly nondegree and study literature. In order to attract international students, the Chinese government has taken several measures, such as providing scholarships, encouraging the provision of English-taught courses, and granting work permits to this population. But China faces challenges in attracting more degree-seeking students.